(untitled) (Mustansiria Dental Journal, 2018)
The facial appearance of patients with β-thalassemia major is readily recognizable so that soft tissue profile analysis is presented in this study. The aim of the study is concerned about the analysis of soft tissue profile morphology in a group of patients having β-thalassemia major and to record the possible differences between both thalassemic genders and to investigate the differences in the soft tissue morphology between thalassemic patients and non thalassemic normal subjects The material of this study consisted from lateral cephalometric radiographs for (40) thalassemic patients aged 15-17 years and (40) cephalometric radiographs for non thalassemic normal subjects were obtained for analyzing soft tissue profile morphology The results showed that there were no significant differences between thalassemic males and females but the soft tissue profile morphology for thalassemic patients mostly different from normal subjects which characterized by convex profile. Thalassemic patients have a soft tissue profile morphology mostly different from normal’s that characterized by smaller nasal dimensions, short and everted upper lip and thicker lower lip which giving them the appearance of convex profile.